ON THE ISSUE OF ANALGESIA IN PATIENTS WITH CANCER OF THE ESOPHAGUS AND CARDIOESOPHAGEAL ZONE - Yusupbekov, A.A.; Khakimov, Ya.Sh.; Yusupbekov, Ah.A.; Usmanov, B.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To identify the best way to increase the effectiveness of postoperative analgesia by assessing the degree of analgesia after open surgery for cancer of the esophagus and cardioesophageal zone. Material and methods: Under observation, there were 85 patients operated on at the Department of Oncology and Radiology of the Ministry of Health of the Republic of Uzbekistan and its Bukhara branch for cardioesophageal cancer and esophageal cancer. There were 57 men (67.0%), 38 women (33.0%), and the average age was 56.4±0.6 years. Results: The introduction of a multimodal approach based on the combined use of NSAIDs and opiates significantly increased the effectiveness of postoperative analgesia. However, in most patients, the intensity of pain exceeded the threshold for adequate analgesia of 4 points. Conclusions: Monitoring of postoperative pain on a digital rating scale helps to adequately determine the strategy of pain management and improve the indicator of medical and psychological rehabilitation of the patient.